A critical study of group-defining categories in the discursive construal of national identity - Shtok, Nina (LingBaW. Linguistics Beyond and Within, 2024)
On 24 February 2022, Russia launched a full-scale military invasion of Ukraine. The beginning of this war marked a significant turning point with far-reaching consequences for the countries involved. Russian political discourse has responded swiftly to the conflict with a marked increase in nationalist rhetoric. This surge underscores a renewed emphasis on national unity and a collective sense of purpose, alongside a growing imperative to safeguard Russian integrity and sovereignty. The discourse has increasingly framed the war as a battle against external threats, positioning Russia as a defender of traditional values and a bulwark against perceived Western encroachments. This nationalist narrative, actively promoted by the government, serves to mobilise public support for its policies. Official speeches by the head of state play a central role in disseminating this ideology. Accordingly, this paper sets out to analyse selected addresses by the Russian President delivered during the conflict’s initial year to uncover the discursive mechanisms shaping Russian national identity. It relies on a discourse-historical approach, which provides effective tools for advancing this endeavour.